Pengaruh Pemahaman Akuntansi, Pemanfaatan Teknologi Informasi Dan Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan Badan Usaha Milik Desa (BUMDes) Se-Kecamatan Sidemen Kabupaten Karangasem - Dewa Ayu Anggitha Sastrawati; Ni Wayan Alit Erlina Wati; Ni Putu Yeni Yuliantari (UNHI Press, 2023)
This study aims to determine the effect of accounting understanding, use of information technology, internal control systems on the quality of BUMDes financial reports in Sidemen District. The research method used is a quantitative research method with primary data obtained from questionnaire data. The population of this study is all BUMDes in Sidemen District. The sampling technique used was purposive sampling with 45 respondents. The data analysis technique used is multiple linear regression which is processed with the help of the SPSS for windows program. The results of this study indicate that partially the level of understanding of accounting, utilization of information technology and internal control system has a positive and significant effect on the quality of financial reports.